CRITIQUE OF THE SORELIAN CONCEPT OF MYTH - Campos, Manuel (2005)
Sorel's theory about the myth is here confronted with that implied in classicmythology. Also, an interpretation ofthe Sorelian myth is here subjected topolitical scrutiny.